Effect of Seasons on the Ccontent of Some Vitamins in Marine Algae at the Beach of Zawia City, Libya - Alzagtat أحميدة; Shtewi عمر; Qarimidah فوزية (Journal of Pure & Applied Sciences, 2022)
This study aims to investigate the quantity of some vitamins dissolved in water, namely vitamin B6, vitamin B12 and vitamin C for six species of marine algae, namely: Enteromorpha compressa from green algae and Pdina pavonica, Cystosiera spinosa, Sargassum vulgare, Dictyota dichotoma from brown algae and Jania rubens from red algae in Zawia, Libya. The different types of algae were collected from four sites in Zawiya area, namely, Dila, Godaim, Al- Harsha, and Al-Mutraid during the seasons (1/9/2013 to 1/9/2014). The results obtained show that the highest amount of vitamin B6 is 1.02 mg/100 mg in Dictyota dichotoma in the Dila site in fall and the highest value of vitamin B12 is 6.72 mg/100 mg in red algae Jania rubens in the Dila site in the summer and the highest value of vitamin C is 0.129 mg/100 mg of Dictyota dichotoma algae in the Dila site in summer. It is also evident through the results of the statistical analysis of this study that there is a high significant correlation at the level of 1% ((P≤ 0.01) between the site and vitamin B12 (0.20), as well as vitamin B12 and algae species (0.30), and vitamin C and algae species (0.42), which indicates however, seasonal climatic and environmental conditions have an impact on the amount of vitamins in different algae species.